A note on the susceptibility of six red raspberry cultivars and Tayberry to fruit infection by late yellow rust - Luffman, M.; Buszard, D. (Phytoprotection, 1990)
Fruit clusters of six red raspberry (Rubus idaeus) cultivars and Tayberry were inoculated in vivo using aeciospores and urediniospores of Pucciniastrum americanum. The response was similar for both inocula. Two raspberry cultivars, Nova and Royalty, and Tayberry were apparently resistant to late yellow rust infection on fruits while the other raspberry cultivars exhibited differing degrees of susceptibility to late yellow rust. The cultivar Boyne exhibited some partial resistance.